HIV-Infected Women's Motivations for Use of Dual Methods of Contraception [21N]. (May 2016) - Delaney, Augustina; Haddad, Lisa
Abstract : INTRODUCTION: Despite World Health Organization recommendations, dual method contraceptive use remains extremely low HIV-infected women. Dual method use is the use of a barrier method along with contraception effective at preventing pregnancy. This study aimed to identify factors influencing dual method use among HIV-infected women in Atlanta, Georgia. METHODS: HIV-infected women ages 18–45 who were sexually active in the past six months completed a 225-item cross-sectional, audio computer assisted self-interview assessing knowledge, attitudes and practices surrounding reproductive health. Logistic regression models were created to compare: 1) dual method use with no dual method use, and 2) dual method use with condom only use. RESULTS: Of 187 participants, 40% used dual methods, 44% used condoms, 8.3% used non-barrier methods, and 7.7% used no effective method. Dual method users were more likely to report having transmitted HIV to a partner, know their viral load, had an HIV positive child, be concerned about ease of birth control use, and have more sexual partners in the past six months. Compared to condom users, dual method users were more likely to have had an unplanned pregnancy and less concerned about birth control prescriptions. CONCLUSION: Past high risk behaviors leading to negative outcomes may be motivating factors for dual method use. Additionally, prescription requirements and ease of use may act as barriers to uptake of dual methods. Discussions with HIV-infected women about reproductive health should include risks of transmission and pregnancy as well as all of the contraceptive options available.